Meridianin C inhibits the growth of YD‐10B human tongue cancer cells through macropinocytosis and the down‐regulation of Dickkopf‐related protein‐3. Issue 12 (24th September 2018) - Park, Nam‐Sook; Park, Yu‐Kyoung; Ramalingam, Mahesh; Yadav, Anil Kumar; Cho, Hyo‐Rim; Hong, Victor Sukbong; More, Kunal N.; Bae, Jae‐Hoon; Bishop‐Bailey, David; Kano, Junko; Noguchi, Masayuki; Jang, Ik‐Soon; et al.
Abstract: Meridianin C is a marine natural product known for its anti‐cancer activity. At present, the anti‐tumour effects of meridianin C on oral squamous cell carcinoma are unknown. Here, we investigated the effect of meridianin C on the proliferation of four different human tongue cancer cells, YD‐8, YD‐10B, YD‐38 and HSC‐3. Among the cells tested, meridianin C most strongly reduced the growth of YD‐10B cells; the most aggressive and tumorigenic of the cell lines tested. Strikingly, meridianin C induced a significant accumulation of macropinosomes in the YD‐10B cells; confirmed by the microscopic and TEM analysis as well as the entry of FITC‐dextran, which was sensitive to the macropinocytosis inhibitor amiloride. SEM data also revealed abundant long and thin membrane extensions that resemble lamellipodia on the surface of YD‐10B cells treated with meridianin C, pointing out that meridianin C‐induced macropinosomes was the result of macropinocytosis. In addition, meridianin C reduced cellular levels of Dickkopf‐related protein‐3 (DKK‐3), a known negative regulator of macropinocytosis. A role for DKK‐3 in regulating macropinocytosis in the YD‐10B cells was confirmed by siRNA knockdown of endogenous DKK‐3, which led to a partial accumulation of vacuoles and a reduction in cell proliferation, and by exogenous DKK‐3 overexpression, which resulted in a considerable inhibition of the meridianin C‐induced vacuole formation and decrease in cell survival. In summary, this is the first study reporting meridianin C has novel anti‐proliferative effects via macropinocytosis in the highly tumorigenic YD‐10B cell line and the effects are mediated in part through down‐regulation of DKK‐3.